2016
DOI: 10.1016/j.clinbiochem.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing urinary hCGβcf patterns during pregnancy

Abstract: Urine specimens with elevated hCGβcf are frequently encountered during pregnancy but hCGβcf excretion patterns are unpredictable. Manufacturers and clinicians must appreciate that hCGβcf is the major immunoreactive component in urine during pregnancy and must design and interpret qualitative urine hCG test results accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…[1] Data obtained from urine samples of 25 pregnant women across all three trimesters found that the pattern of intact hCG and βcf-hCG was highly variable between women. [8] However, a correlation between intact hCG and βcf-hCG was observed, with a similar R-squared value for the regression analysis as that reported in this study (0.70 and 0.72, respectively). Although the results of this study are not directly comparable to the one reported here, as the samples used were collected from routine clinic visits, therefore, they were not necessarily first morning urine and were not collected daily for each woman, as in this study.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…[1] Data obtained from urine samples of 25 pregnant women across all three trimesters found that the pattern of intact hCG and βcf-hCG was highly variable between women. [8] However, a correlation between intact hCG and βcf-hCG was observed, with a similar R-squared value for the regression analysis as that reported in this study (0.70 and 0.72, respectively). Although the results of this study are not directly comparable to the one reported here, as the samples used were collected from routine clinic visits, therefore, they were not necessarily first morning urine and were not collected daily for each woman, as in this study.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies have also reported that intact hCG urinary levels are higher than those of βcf-hCG in early pregnancy and that this situation reverses after~5 weeks of pregnancy. [1,8] Data from a complete pregnancy found that from week 5 to delivery, the concentration of βcf-hCG is approximately 10-fold that of hCG. [1] Data obtained from urine samples of 25 pregnant women across all three trimesters found that the pattern of intact hCG and βcf-hCG was highly variable between women.…”
Section: Discussionmentioning
confidence: 99%
“…It is a heterodimeric glycoprotein consisting of alpha and beta subunits. After undergoing metabolism in the liver and further breakdown in the kidneys, it presents as a beta core fragment to be measured by the POC UPT kits [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…In the urine, an hCG degradation product known as β-core fragment (βcf-hCG) is the major form of hCG during the late first and entire second trimester. 5 The presence of βcf-hCG can cause a false-negative urine hCG test result due to the variant hook effect.…”
Section: Test Characteristicsmentioning
confidence: 99%
“…hCG consists of α and β subunits that circulate as intact or variant forms, such as free α-subunits, free β-subunits, or their degradation products. In the urine, an hCG degradation product known as β-core fragment (βcf-hCG) is the major form of hCG during the late first and entire second trimester . The presence of βcf-hCG can cause a false-negative urine hCG test result due to the variant hook effect.…”
Section: Test Characteristicsmentioning
confidence: 99%